THE IMPORTANCE OF GUIDANCE IN UNDERSTANDING CULTURAL DISCOURSE IN THINKING AND SPEAKING FOR FOREIGN STUDENTS IN BIPA PROGRAM - Tiawati, Refa Lina; Rahmat, Wahyudi; Kemal, Edwar; Chen, Wei (ppjbsip, 2022)
The lack of understanding of cultural discourse in speech is the key to international failure success in understanding language concepts, especially for BIPA learners in Indonesia. This research aims to reveal the importance of understanding the concepts of speech that must be considered in communicating. The method used is qualitative descriptive. The object of this study is an international student from Taiwan named Xing-Qian, who is participating in the Indonesian program for Foreign Speakers (BIPA) at PGRI University of West Sumatra. This research is naturalistic. The data in this study is in the form of video that is the result of recording in the field directly, then using the technique of seeing the record to transcribe the research results into writing form. The results showed that the international students used a form of guidance on the instructions for begging, asking, welcoming, advising, and inviting.